DYNAMICS OF THE RUWAHAN TRADITION IN PALEMBANG MALAY SOCIETY: FROM SPIRITUAL TO COMMERCIAL - Puspita, Fira; Rusli, Ris’an; Lemiyana; Diana (Ikatan Dosen Menulis, 2023)
Culture is a fundamental element in the formation of community identity, including for the Palembang Malay community. One of the cultures possessed by this community is the Ruwahan tradition. This article attempts to provide information about the Ruwahan tradition carried out by the Palembang Malay community as well as convey shifts or changes in the Ruwahan tradition among the Malay community in Palembang. Through the library research method, the author obtained information from various written sources that were relevant to the object of study, namely the Palembang Malay community. The results presented in this paper show that there was a shift in the Ruwahan tradition due to the inclusion of Islamic values in the early Ruwahan tradition which came from Hindu religious heritage. Then there was a change from spiritual ritual activities to commercial and economic aspects as well as the involvement of the Palembang Malay community who became active in commercialization in the current implementation of the Ruwahan tradition.